Campylobacter - Tellez-Isaias, Guillermo; El-Ashram, Saeed (IntechOpen, 2022)
Campylobacter is the major cause of food-borne bacterial diarrheal illnesses worldwide. Many wild and domestic animals carry the organism in their intestines. Intestinal colonization results in the transmission of Campylobacteriosis to healthy animals, and epidemiological studies imply that contaminated animal products contribute to Campylobacteriosis. Interventions in animal production offer the best chance of minimizing illness risk. In addition, implementing enhanced hygiene standards and decontamination can reduce the prevalence of Campylobacter contamination in animal meat. This book investigates Campylobacter's significance as a food-borne pathogen and summarizes recent breakthroughs in isolation, identification, the involvement of immune responses and microbiota, as well as novel control strategies.